Disentangling climatic and anthropogenic controls on global terrestrial evapotranspiration trends. (8th September 2015) - Mao, Jiafu; Fu, Wenting; Shi, Xiaoying; Ricciuto, Daniel M; Fisher, Joshua B; Dickinson, Robert E; Wei, Yaxing; Shem, Willis; Piao, Shilong; Wang, Kaicun; Schwalm, Christopher R; Tian, Hanqin; et al.
Abstract: We examined natural and anthropogenic controls on terrestrial evapotranspiration (ET) changes from 1982 to 2010 using multiple estimates from remote sensing-based datasets and process-oriented land surface models. A significant increasing trend of ET in each hemisphere was consistently revealed by observationally-constrained data and multi-model ensembles that considered historic natural and anthropogenic drivers. The climate impacts were simulated to determine the spatiotemporal variations in ET. Globally, rising CO2 ranked second in these models after the predominant climatic influences, and yielded decreasing trends in canopy transpiration and ET, especially for tropical forests and high-latitude shrub land. Increasing nitrogen deposition slightly amplified global ET via enhanced plant growth. Land-use-induced ET responses, albeit with substantial uncertainties across the factorial analysis, were minor globally, but pronounced locally, particularly over regions with intensive land-cover changes. Our study highlights the importance of employing multi-stream ET and ET-component estimates to quantify the strengthening anthropogenic fingerprint in the global hydrologic cycle.